Atomic Force Microscopy Is a Potent Technique to Study Eosinophil Activation - Eaton, Peter; Amaral, Constança Pais do; Couto, Shirley C. P.; Oliveira, Mariangela S.; Vasconcelos, Andreanne G.; Borges, Tatiana K. S.; Kückelhaus, Selma A. S.; Leite, José Roberto S. A.; Muniz-Junqueira, Maria Imaculada (Frontiers in Physiology, 2019)
Eosinophils are multifunctional cells with several functions both in healthy individuals, and those with several diseases. Increased number and morphological changes in eosinophils have been correlated with the severity of an acute asthma exacerbation. We measured eosinophils obtained from healthy controls and individuals with acute asthma using Atomic Force Microscopy (AFM). In the control samples, cells showed more rounded morphologies with some spreading, while activated cells from symptomatic individuals were spreading, and presenting emission of multiple pseudopods. Eosinophils presenting separate granules close to the cells suggesting some degranulation was also increased in asthma samples. In comparison to histopathological techniques based on brightfield microscopy, AFM showed considerably more details of these morphological changes, making the technique much more sensitive to detect eosinophil morphological changes that indicate functional alteration of this cell. AFM could be an important tool to evaluate diseases with alterations in eosinophil functions.